Failing health. Exploring tensions. - Salter, Leah Karen (Murmurations: Journal of Transformative Systemic Practice, 2023)
Recently I was invited to write a short paper for Context magazine, a magazine for Family Therapy and Systemic Practice in the UK. It is a themed edition, due to be published in the summer of 2023, edited by Joanne Hipplewith who generated the theme of “Failing, to do better” (Context, 187). For me the title speaks to the idea that there is a tension to explore within failure; the tension of present pain and future opportunity that the inclusion of the comma brings into view. I wrote about experiencing the theme as a writing prompt and used the opportunity to reflect on times I have experienced failure in academic contexts and to reflect on the process of writing for publication. For many this can invite anxiety around failure and provoke fear of “getting it wrong”. I explored also the tension between the pain of failure and the hope of learning something useful from the experience (Salter, 2023). A sub-theme emerged in my writing linked to current health status and the recent loss of my father who died from cancer in September 2022. I suppose I was reminded of the invitation to see ill health and end of life as a failure of some kind, that I had been failing in terms of my own health and that my father ultimately had failed to survive cancer. But there were opportunities, even here. My father and I found a way to live with (and for me, live through and beyond) the health challenges we faced and we were able to create space in our relationship to honour each other’s challenges. This was new territory. A new tension.